2006
DOI: 10.1103/revmodphys.78.953
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium: The glass transition and elastic models of glass-forming liquids

Abstract: Basic characteristics of the liquid-glass transition are reviewed, emphasizing its universality and briefly summarizing the most popular phenomenological models. Discussion is focused on a number of alternative models which one way or the other connect the fast and slow degrees of freedom of viscous liquids. It is shown that all these "elastic" models are equivalent in the simplest approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
1,290
1
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,175 publications
(1,352 citation statements)
references
References 182 publications
51
1,290
1
10
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ).…”
Section: Introductionmentioning
confidence: 99%
“…Although these materials are commonly regarded as disordered systems, crucial features of the glass transition, such as the increase in heterogeneity and the larger cooperativity of the liquid dynamics approaching solidification [6][7][8][9] , can be rationalized by the presence of medium-range ordered regions (MRO) in the liquid phase.…”
mentioning
confidence: 99%
“…However, as long as the glasses are chemically similar and thus have the same average intermolecular distance [55], the proportionality is usually observed. Here, we have found a relatively strong correlation (R 2 = 0.87) between G at room temperature and T g,vis for the aluminosilicate glasses (Fig.…”
Section: Test Of the Shoving Modelmentioning
confidence: 99%
“…As the elastic properties are correlated with the short-and intermediate range order [43], here we consider the phenomenological "shoving model" of Dyre et al [51][52][53][54][55], in which the dynamics of the glass-forming liquid are considered to be controlled by the elasticity through the instantaneous (infinite frequency) shear modulus G ∞ . According to the shoving model, the non-Arrhenius scaling of relaxation time (i.e., the fragility) is …”
Section: Introductionmentioning
confidence: 99%